The Role of Literature in Nation Building and Cultural Consciousness - Chidanand M. Aigali (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Literature is a description of human experience that has dimension of personal and social as well as the knowledge of humanity that is parallel to the form of life itself. It is also interpretation or reflection of life. Every nation has its own literature that tells the story of it people, beliefs and struggles. On other hand nation building is a process of uniting people within the state for developing a shared sense of purpose, identity and vision for the future. To achieve this goal everyone, have to conscious about their own culture, tradition and beliefs. On that way literature contributes to the nation building and the growth of cultural consciousness. Literature mirrors the life of people and helps to shape their collective identity by expressing social, political and moral values. It strengthens national feeling, preserves cultural heritage and encourages unity in diversity. In this study an attempt has been made to analyze the relationship between literature, nationality, and cultural awareness by examining key ideas from writers across the world.